Comparative performance of the BGISEQ-500 vs Illumina HiSeq2500 sequencing platforms for palaeogenomic sequencing. Issue 8 (26th June 2017) - Mak, Sarah Siu Tze; Gopalakrishnan, Shyam; Carøe, Christian; Geng, Chunyu; Liu, Shanlin; Sinding, Mikkel-Holger S; Kuderna, Lukas F K; Zhang, Wenwei; Fu, Shujin; Vieira, Filipe G; Germonpré, Mietje; Bocherens, Hervé; et al.
Abstract: Ancient DNA research has been revolutionized following development of next-generation sequencing platforms. Although a number of such platforms have been applied to ancient DNA samples, the Illumina series are the dominant choice today, mainly because of high production capacities and short read production. Recently a potentially attractive alternative platform for palaeogenomic data generation has been developed, the BGISEQ-500, whose sequence output are comparable with the Illumina series. In this study, we modified the standard BGISEQ-500 library preparation specifically for use on degraded DNA, then directly compared the sequencing performance and data quality of the BGISEQ-500 to the Illumina HiSeq2500 platform on DNA extracted from 8 historic and ancient dog and wolf samples. The data generated were largely comparable between sequencing platforms, with no statistically significant difference observed for parameters including level ( P = 0.371) and average sequence length ( P = 0718) of endogenous nuclear DNA, sequence GC content ( P = 0.311), double-stranded DNA damage rate (v. 0.309), and sequence clonality ( P = 0.093). Small significant differences were found in single-strand DNA damage rate (δS; slightly lower for the BGISEQ-500, P = 0.011) and the background rate of difference from the reference genome (θ; slightly higher for BGISEQ-500, P = 0.012). This may result from the differences in amplification cycles used to polymerase chain reaction–amplify the libraries. A significant difference was also observed in the mitochondrial DNA percentages recovered ( P = 0.018), although we believe this is likely a stochastic effect relating to the extremely low levels of mitochondria that were sequenced from 3 of the samples with overall very low levels of endogenous DNA. Although we acknowledge that our analyses were limited to animal material, our observations suggest that the BGISEQ-500 holds the potential to represent a valid and potentially valuable alternative platform for palaeogenomic data generation that is worthy of future exploration by those interested in the sequencing and analysis of degraded DNA.